Opposing actions of the synapse-associated protein of 97-kDa molecular weight (SAP97) and Disrupted in Schizophrenia 1 (DISC1) on Wnt/β-catenin signaling. (21st June 2016) - Boccitto, M.; Doshi, S.; Newton, I.P.; Nathke, I.; Neve, R.; Dong, F.; Mao, Y.; Zhai, J.; Zhang, L.; Kalb, R.
Graphical abstract: Highlights: SAP97 is a novel inhibitor of Wnt-induced β-catenin transcriptional activity. SAP97 may mediate this activity through phosphorylation of GSK3β. Increased DISC1 expression stabilizes SAP97. Abstract: It has been suggested that synapse-associated protein of 97-kDa molecular weight (SAP97) is a susceptibility factor for childhood and adult neuropsychiatric disorders. SAP97 is a scaffolding protein that shares direct and indirect binding partners with the Disrupted in Schizophrenia 1 ( DISC1 ) gene product, a gene with strong association with neuropsychiatric disorders. Here we investigated the possibility that these two proteins converge upon a common molecular pathway. Since DISC1 modifies Wnt/β-catenin signaling via changes in glycogen synthase kinase 3 beta (GSK3β) phosphorylation, we asked if SAP97 impacts Wnt/β-catenin signaling and GSK3β phosphorylation. We find that SAP97 acts as inhibitor of Wnt signaling activity and can suppress the stimulatory effects of DISC1 on β-catenin transcriptional activity. Reductions in SAP97 abundance also decrease GSK3β phosphorylation. In addition, we find that over expression of DISC1 leads to an increase in the abundance of SAP97, by inhibiting its proteasomal degradation. Our findings suggest that SAP97 and DISC1 contribute to maintaining Wnt/β-catenin signaling activity within a homeostatic range by regulating GSK3β phosphorylation.